Rancang Bangun Aplikasi Perpustakaan Di Smk Negeri 1 Cerme - Ariansyah, Yudha Putra; Jusak, DR.; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
A Library is considered as a place for education, research, preservation, information, and recreation in order to improve intelligence and empowerment of the nation. Currently there are some core processes at SMK Negeri 1 Cerme library, namely: books inventory records, books loan and return, records of infringement, books procurement process and the books destruction records. The absence of catalog in the library becomes major problem since people may spare a lot time to search books. In the book return process, lack of reminder of the due date causes the book borrower sometimes forget to return the books on time. In addition to that, manual record can lead to unsyncronized data beetween the currently existing stock and the reports such as, destruction report and book inventory. In this study, we develope a computerized library application at SMK Negeri 1 Cerme Library that is expected to be able assist the registration, loan and returns transactions. A reminder in added utilizing the SMS Gateway to remind the borrowers. The catalog can also help the students to reduce the time for books searching. Finally, automatic reports would make it easier to be distributeed to the head of library.